Upper secondary school students' conceptions of learning, learning strategies, and academic achievement - Vettori, Giulia; Vezzani, Claudio; Bigozzi, Lucia; Pinto, Giuliana (The Journal of educational research (Washington, D.C.), 2020)
The relations between more surface- or deep-level learning approaches and academic achievement were investigated. Gender, level of study, and type of schools were moderating variables. 170 upper-secondary school students' conceptions of learning and their chosen learning strategies were explored via two self-report questionnaires. Furthermore, their academic achievement in a range of subject areas was collected. A Confirmatory Factorial Analysis of the two questionnaires' dimensions identified two factors showing learning approaches of different qualitative nature, more surface- or deep-level. Then, General Linear Models showed that the predictive impact of the tracked factors was differently related to students' academic achievement. The factor "Deep metacognitive theory of learning" positively predicted academic achievement, whereas the factor "Surface metacognitive theory of learning" was a negative predictor.